2021
DOI: 10.18632/aging.203465
|View full text |Cite
|
Sign up to set email alerts
|

High red blood cell distribution width levels could increase the risk of hemorrhagic transformation after intravenous thrombolysis in acute ischemic stroke patients

Abstract: The association between the red blood cell distribution width (RDW) and hemorrhagic transformation (HT) after thrombolysis in acute ischemic stroke patients remains inconclusive. Our study aimed to assess whether high RDW levels are associated with the occurrence of HT after thrombolysis. Data were consecutively collected and retrospectively analyzed for stroke patients treated with thrombolysis between 1 January 2017 and 31 December 2019. The primary outcomes were the occurrence of HT and symptomatic HT. Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
0
10
1
Order By: Relevance
“…A meta-analysis displayed that the baseline levels of RDW might be a predictor of stroke occurrence and outcome ( 30 ). What is more, high RDW levels may increase the risk of hemorrhagic transformation after intravenous thrombolysis in AIS patients ( 31 ). Nowadays, the levels of RDW were found to be linked to post-stroke depression ( 16 ), another common emotional complication after the onset of AIS.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis displayed that the baseline levels of RDW might be a predictor of stroke occurrence and outcome ( 30 ). What is more, high RDW levels may increase the risk of hemorrhagic transformation after intravenous thrombolysis in AIS patients ( 31 ). Nowadays, the levels of RDW were found to be linked to post-stroke depression ( 16 ), another common emotional complication after the onset of AIS.…”
Section: Discussionmentioning
confidence: 99%
“…HT is the most common complication of AIS patients undergoing IVT therapy and RDW levels are the predictor for the occurrence of HT after thrombolysis [ 12 , 24 , 42 ]. The prevalence of HT in our cohort was 34 (8.06%).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, RDW has been recognized as a biomarker for vascular diseases [20,21]. Previous studies have noted that RDW is a potential independent risk factor for predicting cardiovascular and cerebrovascular diseases [22][23][24][25][26][27]. A recent study has suggested that AIS patients with increased RDW has higher occurrence of HT [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 Besides, a large number of studies have appeared a near affiliation between poor clinical outcomes and high RDW levels in the intense stage of maladies such as stroke, and hemorrhagic transformation in acute ischemic stroke patients who have experienced intravenous thrombolysis. 16 , 17 Similarly, Kim et al found that higher RDW levels at admission were related to a 3-month poor functional prognosis in patients with AIS treated with intravenous thrombolysis. 18 Additionally, a close association has been shown between depression and RDW.…”
Section: Introductionmentioning
confidence: 96%